2019
DOI: 10.1038/s41598-019-51984-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of codon optimization on coagulation factor IX translation and structure: Implications for protein and gene therapies

Abstract: Synonymous codons occur with different frequencies in different organisms, a phenomenon termed codon usage bias. Codon optimization, a common term for a variety of approaches used widely by the biopharmaceutical industry, involves synonymous substitutions to increase protein expression. It had long been presumed that synonymous variants, which, by definition, do not alter the primary amino acid sequence, have no effect on protein structure and function. However, a critical mass of reports suggests that synonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 71 publications
0
40
0
1
Order By: Relevance
“…The complete ribosome profiling pipeline analysis is described in Figure 1: Sequencing data were pre-processed and aligned as described by Alexaki et al 5 as well as the step by step guide found in the README.txt accessible on GitHub.…”
Section: Ribosome Profilingmentioning
confidence: 99%
See 4 more Smart Citations
“…The complete ribosome profiling pipeline analysis is described in Figure 1: Sequencing data were pre-processed and aligned as described by Alexaki et al 5 as well as the step by step guide found in the README.txt accessible on GitHub.…”
Section: Ribosome Profilingmentioning
confidence: 99%
“…In doing so, the amino acid sequence of the protein remains unaltered, therefore these changes were assumed to be inconsequential for the structure and function of the protein. However, this is not always true; through our ribosome profiling study, we described that these synonymous changes drastically altered translational kinetics and led to protein conformational changes 5 .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations